2018
DOI: 10.1002/ecy.2173
|View full text |Cite
|
Sign up to set email alerts
|

Invasive predator tips the balance of symmetrical competition between native coral‐reef fishes

Abstract: The importance of competition and predation in structuring ecological communities is typically examined separately such that interactions between these processes are seldom understood. By causing large reductions in native prey, invasive predators may modify native species interactions. I conducted a manipulative field experiment in The Bahamas to investigate the possibility that the invasive Pacific red lionfish (Pterois volitans) alters competition between planktivorous fairy and blackcap basslets (Gramma lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 87 publications
2
5
0
Order By: Relevance
“…In contrast, P. megacephala invasion generates a landscape of unoccupied, low‐reward host plants, which shifts competition among acacia ants to the colony founding stage, favoring more strongly colonizing species with lower energetic requirements. Our results are consistent with other studies demonstrating that invasive species can facilitate natives (Rodriguez 2006, Collins et al 2017, Kindinger 2018, Goodman and Warren 2019, Rees et al 2019). For example, Kindinger (2018) showed that invasive lionfish ( Pterois volitans ) facilitated the native blackcap basslet ( Gramma melacara ) through differential predation on the basslet’s competitor on Bahamian reefs.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, P. megacephala invasion generates a landscape of unoccupied, low‐reward host plants, which shifts competition among acacia ants to the colony founding stage, favoring more strongly colonizing species with lower energetic requirements. Our results are consistent with other studies demonstrating that invasive species can facilitate natives (Rodriguez 2006, Collins et al 2017, Kindinger 2018, Goodman and Warren 2019, Rees et al 2019). For example, Kindinger (2018) showed that invasive lionfish ( Pterois volitans ) facilitated the native blackcap basslet ( Gramma melacara ) through differential predation on the basslet’s competitor on Bahamian reefs.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with other studies demonstrating that invasive species can facilitate natives (Rodriguez 2006, Collins et al 2017, Kindinger 2018, Goodman and Warren 2019, Rees et al 2019). For example, Kindinger (2018) showed that invasive lionfish ( Pterois volitans ) facilitated the native blackcap basslet ( Gramma melacara ) through differential predation on the basslet’s competitor on Bahamian reefs. Reductions in the competitor’s abundance allowed the blackcap basslets to occupy more favorable foraging territories on the reef, leading to higher growth rates of this fish in the presence of the invader.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition to exerting non-consumptive effects, lionfish can also be subjected to these effects by humans; lionfish hide deeper in the reef and are more wary of humans as a consequence of lionfish culling programs [37,38]. Lionfish also exert non-consumptive effects through 'transmitter' species, for example lionfish predation on fairy basslet releases blackcap basslet from competition and allows them to occupy prime feeding locations on the reef [39]. Another type of non-consumptive impact is competition.…”
Section: Introductionmentioning
confidence: 99%
“…Intraspecific competition is thought to be more intense than interspecific competition due to the similar characteristics of individuals from the same species (Connell, 1983). Because it is such an important selection force, competition is often considered a main evolutionary driver of behavioural and physiological traits, as well as a key factor in affecting community structure (Connell, 1961;Bonin et al, 2015;Kindinger, 2018).…”
Section: Chapter 1 -Introductionmentioning
confidence: 99%